Dynamic carpooling notification system for rural areas - Alharbi, Omar; Hashim, Nor Laily (2009)
With the increasing of energy resource's prices these days, the demands of energy resources already decreased in most countries of the world in general especially fuel resource.Beside that, rural areas in various countries suffer from lack of transportation services. Therefore, Dynamic Carpooling Notification System (DCNS) by using mobile phone is proposed to overcome such problems, by allowing many passengers and drivers to be matched with each other instantly. By using mobile phone, an automatic process will be created in which drivers and passengers are matched to a shared ride wherever and whenever they need it.This paper describes the initial stage of this system by discussing the functionalities of this prototype.